2022
DOI: 10.1007/s12144-022-02854-0
|View full text |Cite
|
Sign up to set email alerts
|

European university students’ mental health during Covid-19: Exploring attitudes towards Covid-19 and governmental response

Abstract: The effects of Covid-19 have been felt worldwide and one population that are of increasing concern are university students. University students have endured unique and drastic changes to their everyday and academic lives. It is important to understand how university students in different parts of the world have been affected by the Covid-19 pandemic and how it has affected their mental health? A cross-sectional study was conducted during the first wave of Covid-19, in May 2020 with 2,006 university students fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
(65 reference statements)
2
14
0
1
Order By: Relevance
“…However, the satisfaction of basic needs is a guarantee of a stable level of mental health. Studies have shown that during the epidemic, there was a significant increase in levels of anxiety and depression among the student population, and the amount of time spent on screens per day changed significantly from the pre-epidemic period (9)(10)(11)(12). The reasons for this have been explored by numerous scholars, with students' lack of self-control, the use of online teaching and learning, and the adverse effects of unmet psychological needs and increased isolation of students due to COVID-19-related restrictions all being risk factors for increased problematic smartphone use among students (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, the satisfaction of basic needs is a guarantee of a stable level of mental health. Studies have shown that during the epidemic, there was a significant increase in levels of anxiety and depression among the student population, and the amount of time spent on screens per day changed significantly from the pre-epidemic period (9)(10)(11)(12). The reasons for this have been explored by numerous scholars, with students' lack of self-control, the use of online teaching and learning, and the adverse effects of unmet psychological needs and increased isolation of students due to COVID-19-related restrictions all being risk factors for increased problematic smartphone use among students (13).…”
Section: Introductionmentioning
confidence: 99%
“…Although the present results clearly support comparable positivity among students in the first and second COVID-19 waves, it is appropriate to acknowledge the limitation that there is no comparative data from before the pandemic. Allen et al (2022) compared students from the UK, Germany, Italy and Spain during the COVID-19 pandemic. The German students reported the highest level of positivity, which may be due to the fact that Germany was in the phase of easing restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that our study was carried out after the outbreak of the Covid-19 pandemic. This pandemic has substantially affected management practices (e.g., social distancing and quarantine policies), teachers’ teaching methods (e.g., transferring traditional classroom teaching to online teaching), and students’ mental health (e.g., anxiety and depression) in higher education worldwide (Allen et al, 2022 ; Tao et al, 2022 ). The negative effects can be particularly salient for international students, including those sojourning in China (English et al, 2022 ; Meng et al, 2022 ).…”
Section: Limitations and Future Research Recommendationsmentioning
confidence: 99%